2000
DOI: 10.1023/a:1008931906253
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this study was to investigate the role of dispositional optimism (DO) as a predictor of health-related quality of life (HRQL) in a sample of upper aerodigestive tract cancer (UADT) patients. A prospective observational study design was used with a cohort of patients from one centre. DO was evaluated using a French version of the Life Orientation Test (the FLOT) translated and validated for this study. HRQL was evaluated using the EORTC QLQ-C30 prior to and 3 months following treatment. The associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(40 citation statements)
references
References 24 publications
3
30
0
7
Order By: Relevance
“…Both optimism and social support have previously been found to be related to better coping post-transplant and higher HRQOL following HSCT [9,[13][14][15] and in other patient groups [16][17][18][19][20][21]. Similarly, in an earlier qualitative study exploring the meaning of HRQOL for HSCT patients [22], seven themes were identified that positively influenced HRQOL, including social support, a positive attitude, and having goals, as identified in this study.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Both optimism and social support have previously been found to be related to better coping post-transplant and higher HRQOL following HSCT [9,[13][14][15] and in other patient groups [16][17][18][19][20][21]. Similarly, in an earlier qualitative study exploring the meaning of HRQOL for HSCT patients [22], seven themes were identified that positively influenced HRQOL, including social support, a positive attitude, and having goals, as identified in this study.…”
Section: Discussionsupporting
confidence: 68%
“…Patients described making downwards comparisons with fellow patients or hypothetical others who were worse off than themselves. For 5 (26% of 19), this was upsetting, as it brought home their own mortality, but for 9 (47% of 19), it also made them appreciate their situation and see it more positively, 'I just count myself as being lucky that I had a perfect match with me brother. People I've known haven't had matches with their own brothers and they've got matches-in fact one from America.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, optimism predicted resilience against distress during the full year. A study of head and neck cancer patients yielded similar results (Allison, Guichard, & Gilain, 2000). Patients were assessed before treatment and three months afterward.…”
Section: Optimism and Subjective Well-beingmentioning
confidence: 64%
“…Only a few studies have investigated the association between optimism and cancer-related fatigue in cancer patients (Allison, Guichard, & Gilain, 2000;Chambers et al, 2012;Kurtz, Kurtz, Given, & Given, 2008;Levkovich, Cohen, Pollack, Drumea, & Fried, 2015;Matthews et al, 2012), and the results are inconsistent. Only two of these studies found an association between a high level of optimism and lower levels of fatigue (Allison et al, 2000;Chambers et al, 2012). The reasons for this could be that the study samples included patients at various stages of their cancer treatment, different cancer diagnosis, or the inconsistencies may stem from methodological issues.…”
mentioning
confidence: 99%